Preliminary systematic literature review on the adoption of Security as a Service (SECaaS) - Tanko, Mohammed Yahaya; Md Sultan, Abu Bakar; Zulzalil, Hazura; Osman, Mohd Hafeez (European Chemical Journal, 2023)
Security as a Service (SECaaS) involves delivering security applications and services via the cloud computing technology to consumers, known as subscribers. Inspired by software as a Service (SaaS), the SECaaS approach promises to provide a high level of security and resources saving. Recent studies revealed numerous benefits of SECaaS as an efficient security model for SaaS applications. However, there is little research about its current adoption and future development. This paper aims to present fill these gaps by conducting a Systematic Literature Review (SLR) that summarizes and analyzes current and past SECaaS development and adoption. The analysis involves classification according to an enhanced SECaaS taxonomy. The SLR began with searching all related literature from well-known online repositories published between January 2011 and October 2021. Furthermore, identified inclusion-exclusion criteria were applied to filter the relevant articles. The study has so far obtained a total of 19 papers from 663 papers that exactly met all the stated criteria. The analysis revealed five concerns by potential SaaS tenants about the adoption of SECaaS and five key factors that make SECaaS as a preferred security mechanism over traditional approaches. Apart from that, seven metrics was identified to evaluate SECaaS performances. Finally, the preliminary findings concluded that SECaaS is a promising solution and more thorough study is needed to further understand the benefits of SECaaS.